2018
DOI: 10.1016/j.virol.2018.07.025
|View full text |Cite
|
Sign up to set email alerts
|

HaCaT epithelial cells as an innovative novel model of rhinovirus infection and impact of clarithromycin treatment on infection kinetics

Abstract: The in vitro propagation of human rhinoviruses (RVs) is difficult because only few continuous human cell lines are permissive to these agents. We propose an innovative model of epithelial cell infection using a non-transformed continuous keratinocyte line from human origin (HaCaT cells). After infection with RV-A13, RV-A16 or RV-A19, HaCaT cells produced infectious particles without showing any observable cytopathic effect and overexpressed ICAM-1 (intercellular adhesion molecule 1), the major entry receptor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…One of the main criticisms of previously published data was that drug concentrations for viral inhibition used in vitro are difficult to translate clinically due to side effects that would occur at those concentrations. The synergy between hydroxychloroquine and azithromycin that we observed herein is at concentrations achieved in vivo and detected in serum [35] and pulmonary tissues (36)(37) respectively. Our data are thus in agreement with the clinical efficacy of the combination of hydroxychloroquine and azithromycin observed by Gautret et al [33].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…One of the main criticisms of previously published data was that drug concentrations for viral inhibition used in vitro are difficult to translate clinically due to side effects that would occur at those concentrations. The synergy between hydroxychloroquine and azithromycin that we observed herein is at concentrations achieved in vivo and detected in serum [35] and pulmonary tissues (36)(37) respectively. Our data are thus in agreement with the clinical efficacy of the combination of hydroxychloroquine and azithromycin observed by Gautret et al [33].…”
Section: Discussionmentioning
confidence: 62%
“…And in enlarge viral infection context, azithromycin was associated to up-regulate interferons I and III [30]. Concerning the respiratory syncytial virus, it was also shown that Macrolides reduce the acidity of the lysosome and by the down-regulation of the ICAM-1 protein (36). So, in the SARS-CoV 2 context, azithromycin could potentialize the effect of hydroxychloroquine by similar mechanism.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This could be explained by the fact that accumulation or high binding between the surface glycoprotein and the receptor does not necessarily trigger post-binding events that allow viral entry, due to the possible presence of restriction factors or lack of other genes expression required for viral infection (27,28). Another probable reason for the absence of CPE in HaCaT cells infected with rVSV-dG-RABV-GFP might be due to the conservation of HaCaT cell integrity as previously observed in HaCaT cells infected with rhinovirus (29). The receptor preference results on HaCaT cells suggested enhanced binding and replication of RABV upon interacting with nAChR, mGluR2 and ITGB1 receptors.…”
Section: Discussionmentioning
confidence: 71%
“…Another probable reason for the absence of CPE in HaCaT cells infected with rVSV-dG-RABV-GFP might be due to the conservation of HaCaT cell integrity as previously observed in HaCaT cells infected with rhinovirus (29). The receptor preference results on…”
Section: Discussionmentioning
confidence: 83%